The Effect To Accountability on The Effectiveness and Transparency of Financial Reports for the 2019 - 2022 Period (Empirical Study at Lazismu Central Office) - Nurma, Eva Septya; Meinarsih, Triana (Journal of Applied Business, Taxation and Economics Research, 2023)
The Influence of Accountability on the Effectiveness and Transparency of Financial Reports for the 2019 – 2022 Period (Empirical Study at the Lazismu Central Office). This research aims to determine the influence of each variable, namely Accountability for Effectiveness and Transparency of Financial Reports. The type and source of data in this research is a quantitative approach with primary data where the data collection method uses a questionnaire method distributed within the Central Amil Zakat Infaq da Shodaqoh Muhammadiyah Institute. The independent variable in this research is Accountability (X1), and the dependent variables are Effectiveness (Y1) and Transparency (Y2). The sample method used was nonprobability sampling, and 70 respondents were obtained. The results of this research are: 1) Accountability of Financial Reports has a significant positive effect on the effectiveness of financial reports, as shown by the results of hypothesis testing which shows a value of 0.876 with a T-Statistics value of 13,661, which means it is calculated to be smaller than T-Statistics. 2) Financial Report Accountability has a significant positive effect on financial report transparency, which is shown by the results of the hypothesis testing carried out, namely showing a result of 0.855 with a T-Statistics value of 17,658, which means it is calculated to be smaller than the T-Statistics.